PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF DAN PENGUASAAN KONSEP SISWA PADA MATERI LARUTAN PENYANGGA - Wulandari, Mrs Wiwin; Liliasari, Mrs; Supriyanti, Mrs Titin (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2011)
The purposes of this research are to increase creative thinking skills and concept mastery of students in the material buffer solution using Problem Based Learning (PBL) model. The method which is used quasi experiment method with one group pretest âposttest design. The research subjects were 31 students in grade XI school stubs on one of the main international school in the town of Cimahi, West Java. The techniques of data collection are done through a written test like 12 essay question, student worksheets, student questionnaires and teacher interviews. The data is analyzed by statistical tests using SPSS version 16.00 and a descriptive analysis. The results showed that the learning process according with 5 stages in the PBL model; over all creative thinking skills and concept mastery increased significantly with the average N-gain = 0.61; indicators of creative thinking skills that experienced the highest increasing is âelaborationâ, N-gain = 0,70; label concepts that experienced the highest increasing is the calculation of pH buffer solution, N-gain=0.86 and PBL model got a positive response from teachers and students.Keywords: buffer solution, creative thinking skills, concepts mastery, problem based learning